Usefulness of Anti-Müllerian Hormone in Polycystic Ovarian Syndrome in Infertile Women - Rijal, Hima (Nepal Journal of Obstetrics and Gynaecology, 2019)
Aims: To correlate the AMH level with various clinical and biochemical parameters in patients presenting to infertility clinic with diagnosis of PCOS. Methods: This is a hospital based prospective study carried out in the Department of Obstetrics and Gynecology, Tribhuvan University Teaching Hospital from January 2018 to December 2018. Women of reproductive age (21– 35 years) who presented to infertility clinic were recruited for study after taking informed consent. PCOS patients were selected by the Rotterdam criteria. Data regarding menstrual history, clinical manifestations of hyperandrogenism, transvaginal ultrasound (TVS) assessments for ovarian follicles, and the levels of AMH, LH, FSH, testosterone and Estradiol were collected. Blood sampling for hormone measurement (LH, FSH, Testosterone, Estradiol) was performed in the second day of menstrual cycle. Serum AMH was measured in any day of menstrual cycle. TVS was performed for morphology of ovaries during follicular phase. Results: There were 54 patients with PCOS based on Rotterdem criteria. The mean age was 26.6±3.7 year (range=20-35). Among the study population 42 patients (78%) had primary infertility. High AMH with bilateral polycystic ovaries was in 32(59.2%), bilateral PCO with normal AMH was in 13(24%), unilateral polycystic ovaries with high AMH was in 2(3.7%). AMH mean value was 9.8±4.1 ng/ml (range=2.8-19.8), high in 40 women (74%) and normal in 14 women (26%). Conclusions: Serum AMH can be a useful serum marker of PCOS and it correlates with the clinical and biochemical abnormalities in women with PCOS. Keywords: anti mullarian hormone, infertility, hyperandrogenism, polycystic ovarian syndrome